Pendampingan Peningkatan Digital Branding pada Berdikari Kopi Melalui Digitalisasi Bisnis - Haifa Atiqah; Prisca Nabila Putri; Pupung Purnamasari (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital branding is the process of building and framing a business brand online, especially using social media such as Instagram, YouTube, TikTok, Facebook, and many more. By getting to know customers more closely, communication becomes easier than before, this is one of the keys to success for all businesses. The objectives of this service activity include knowing how to use social media in online-based business marketing and knowing how to apply social media as an online marketing medium in the era of globalization. The method used is assistance to business actors regarding the importance of applying social media as a means of promoting products among the public. The results of this mentoring activity support that business digitalization can increase the role of digital branding, through the use of social media access so that it can facilitate the reach of target markets in business development and also as a way to help increase revenue at Berdikari Kopi, and can compete globally, and contribute to the opening of jobs for the surrounding community.